2015
DOI: 10.1016/j.chieco.2014.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding financial inclusion in China

Abstract: We use data from the World Bank Global Findex database for 2011 to analyze financial inclusion in China, including comparisons with the other BRICS countries. We find a high level of financial inclusion in China manifested by greater use of formal account and formal saving than in the other BRICS. Financial exclusion, i.e. not having a formal account, is mainly voluntary. The use of formal credit is however less frequent in China than in the other BRICS. Borrowing through family or friends is the most common w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

30
191
2
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 307 publications
(237 citation statements)
references
References 16 publications
(13 reference statements)
30
191
2
14
Order By: Relevance
“…In China, Fungáčová & Weill (2015) found that higher income and better education are associated with greater use of formal accounts and formal credit. In Argentina, Tuesta, Sorensen, Haring & Camara, (2015) showed that education and income are all important variables for financial inclusion.…”
Section: Theory and Review Of Literaturementioning
confidence: 99%
“…In China, Fungáčová & Weill (2015) found that higher income and better education are associated with greater use of formal accounts and formal credit. In Argentina, Tuesta, Sorensen, Haring & Camara, (2015) showed that education and income are all important variables for financial inclusion.…”
Section: Theory and Review Of Literaturementioning
confidence: 99%
“…According to the authors nations whose GDP per capita are low experience poor connectivity and low level of literacy have lower level of financial inclusion. Using China sample Fungáčová & Weill [24] shows level of education and income to significantly affect financial inclusion. The authors report high education level and income as the significant factors which determine financial inclusion in China.…”
Section: Related Literaturementioning
confidence: 99%
“…Sarma, 2008;Chattopadhyay, 2011;Gupte, Venkataramani, & Gupta, 2012;Arora, 2014;Chakravarty & Pal, 2013;Wang & Guan, 2017) and (ii) what factors are associated with financial inclusion (refer to, e.g. Beck & De la Torre, 2006;Chithra & Selvam, 2013;Martinez, Hidalgo, & Tuesta, 2013;Leeladhar, 2006;Rao, 2007;Chakravarty & Pal, 2013;Fungáčová & Weill, 2015;Swamy, 2014;Corrado & Corrado, 2015;Honohan, 2008;Sahoo, Pradhan, & Sahu, 2017;Wang & Guan, 2017;Burgess & Pande, 2005;Levine, 2005).…”
mentioning
confidence: 99%
“…Finally, we took care to use the majority of accessible variables which is involved in many studies in the literature (refer to, e.g. Beck & De la Torre, 2006;Chithra & Selvam, 2013;Martinez et al, 2013;Leeladhar, 2006;Rao, 2007;Chakravarty & Pal, 2013;Fungáčová & Weill, 2015;Swamy, 2014;Corrado & Corrado, 2015;Honohan, 2008;Sahoo et al, 2017;Wang & Guan, 2017;Burgess & Pande, 2005;Levine, 2005). We also used Bank Stability Indexes generated by authors and The Worldwide Governance Indicators from World Bank as the explanatory variables to decipher which factors explain the changes in IFI scores.…”
mentioning
confidence: 99%